Evaluating the Levels of Performance of the Small Scale Contractors in Nigeria - Gambo, Nuru; Said, Ilias; Ismail, Radzi (School of Social Sciences, 2015)
This study is aimed at evaluating the performance levels of small scale contractors (SSC) in Nigeria. Previous studies focused most attention on benchmarking the performance of contractors which were mostly conceptual rather than from any empirical findings, this continuous to pose a challenge to the sustainable development of construction industries particularly in developing countries like Nigeria. There is need to identify the performance levels of these contractors that is the journey so far achieved in the establishment of strong and viable industry for rapid development of socio-economic standards of these countries. The overall performance of small scale contractor (OPC) comprises of financial, technical and managerial performances and the performance of each contractor was evaluated using five point likert scale to obtain the mean performance level in respect to those three classes of performances. Questionnaire survey were administered to the major stakeholders in the Nigerian construction industry comprises of clients, contractors and consultants selected using proportionate stratified random sampling and the results indicated that financial performance had a mean value of 3.58, technical performance was 3.56 and the managerial performance 3.84 means. The three classes of performances fall into the categories of average performing contractors. The study concluded that small scale contractors in Nigerian construction industry (SSC) were average performing contractors and there were significant differences between the contractors’ levels of performances. The study recommended the introduction of project clients’ support with advance to mediate between the major factors affecting cost and the levels of contractors’ performances; this would enhance the rapid development of small scale construction business in Nigeria.